Comparative and Evolutionary Physiology of Vasopressin/ Oxytocin-Type Neuropeptide Signaling in Invertebrates - Odekunle, Esther A.; Elphick, Maurice R. (Frontiers in Endocrinology, 2020)
The identification of structurally related hypothalamic hormones that regulate blood pressure and diuresis (vasopressin, VP; CYFQNCPRG-NH2) or lactation and uterine contraction (oxytocin, OT; CYIQNCPLG-NH2) was a major advance in neuroendocrinology, recognised in the award of the Nobel Prize for Chemistry in 1955. Furthermore, the discovery of central actions of VP and OT as regulators of reproductive and social behaviour in humans and other mammals has broadened interest in these neuropeptides beyond physiology into psychology. VP/OT-type neuropeptides and their G-protein coupled receptors originated in a common ancestor of the Bilateria (Urbilateria), with invertebrates typically having a single VP/OT-type neuropeptide and cognate receptor. Gene/genome duplications followed by gene loss gave rise to variety in the number of VP/OT-type neuropeptides and receptors in different vertebrate lineages. Recent advances in comparative transcriptomics/genomics have enabled discovery of VP/OT-type neuropeptides in an ever-growing diversity of invertebrate taxa, providing new opportunities to gain insights into the evolution of VP/OT-type neuropeptide function in the Bilateria. Here we review the comparative physiology of VP/OT-type neuropeptides in invertebrates, with roles in regulation of reproduction, feeding and water/salt homeostasis emerging as common themes. For example, we highlight recent reports of roles in regulation of oocyte maturation in the sea-squirt Ciona intestinalis, extraoral feeding behaviour in the starfish Asterias rubens and energy status and dessication resistance in ants. Thus, VP/OT-type neuropeptides are pleiotropic regulators of physiological processes, with evolutionarily conserved roles that can be traced back to Urbilateria. To gain a deeper understanding of the evolution of VP/OT-type neuropeptide function it may be necessary to not only determine the actions of the peptides but also to characterise the transcriptomic/proteomic/metabolomic profiles of cells expressing VP/OT-type precursors and/or VP/OT-type receptors within the framework of anatomically and functionally identified neuronal networks. Furthermore, investigation of VP/OT-type neuropeptide function in a wider range of invertebrate species is now needed if we are to determine how and when this ancient signalling system was recruited to regulate diverse physiological and behavioural processes in different branches of animal phylogeny and in contrasting environmental contexts.